(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the factors associated with adherence to antibiotic therapy in patients treated at the Nucleus for Health Care and Professional Practices (NASPP) in Guanambi BA. Methods: This is a descriptive research, with quantitative field analyses. The research subjects were 202 patients from the Center for Health Care and Professional Practices (NASPP) in the municipality, randomly selected, who were given a questionnaire with direct and objective questions related to the interests of the study. The procedure used respected and considered international norms for experimentation with humans, having been approved by the Ethics Committee. Results and Conclusion: It was evidenced that the therapeutic adherence of antibiotics is multifactorial, with the female gender being more prevalent in the use of antibiotics. It was noticed that the higher the level of education, the better the therapeutic adherence. It was also observed that younger patients had a better perception of their health status when compared to older ones, providing better adherence to therapeutic conduct.